FRI0340 COMPARISON OF SECUKINUMAB VERSUS ADALIMUMAB EFFICACY ON SKIN OUTCOMES IN PSORIATIC ARTHRITIS: 52-WEEK RESULTS FROM THE EXCEED STUDY. (2nd June 2020) - Gottlieb, A. B.; Behrens, F.; Nash, P.; Merola, J. F.; Ding, K.; Pellet, P.; Pricop, L.; Mcinnes, I.
Abstract : Background: Psoriatic arthritis (PsA) is a heterogeneous disease comprising musculoskeletal and dermatological manifestations, especially plaque psoriasis. 1 Secukinumab (SEC), an IL-17A inhibitor, provided significantly greater PASI 75/100 responses in a head-to-head trial versus (vs. ) etanercept, a TNF inhibitor, in patients (pts) with moderate-to-severe plaque psoriasis. 2 The objective of the EXCEED study (NCT02745080 ) was to investigate whether SEC is superior to adalimumab (ADA), a TNF inhibitor, as monotherapy in biologic-naive active PsA pts with active plaque psoriasis (defined as having at least one psoriatic plaque of ≥2 cm diameter or nail changes consistent with psoriasis or documented history of plaque psoriasis). Objectives: To report the pre-specified skin outcomes from the EXCEED study in the subset of pts with at least 3% body surface area (BSA) affected with psoriasis at baseline. Methods: Head-to-head, phase-3b, randomised, double-blind, active-controlled, multicentre, parallel-group trial: pts were randomised to receive SEC 300 mg subcutaneous at baseline, Week 1-4, followed by dosing every 4 weeks (q4w) until Week 48 or ADA 40 mg subcutaneous at baseline followed by same dosing q2w until Week 50. The primary endpoint was superiority of SEC vs. ADA on ACR20 response at Week 52. Pre-specified outcomes included the proportion of pts achieving a combined ACR50 and PASI 100 response, PASI 100 response, and absolute PASI score ≤3. Missing data was handled using multiple imputation. Results: 853 pts were randomised to receive SEC (n=426) or ADA (n=427). At baseline, there were 215 and 202 pts having at least 3% BSA affected with psoriasis in the SEC and ADA groups, respectively. A higher proportion of patients achieved simultaneous improvement in ACR50 and PASI 100 response with SEC vs. ADA (30·7% vs. 19·2%; P=0·0087 [Figure]). Higher efficacy was demonstrated for SEC vs. ADA for PASI 100 responses and for the proportion of pts achieving absolute PASI score ≤3 (Table). Conclusion: In this pre-specified analysis, SEC provided higher responses compared to ADA in achievement of simultaneous improvement of joint and skin disease (combined ACR50 and PASI 100 response) and in skin specific endpoints (PASI 100 and PASI score ≤3) at Week 52. References: [1]Coates LC and Helliwell PS. Clinical Med .2017;17:65–70. [2]Langley RG et al. N Engl J Med. 2014;371:326–38. Acknowledgments: Suchita Dubey (Novartis) provided medical writing support. Disclosure of Interests: Alice B Gottlieb Grant/research support from:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Consultant of:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Speakers bureau:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Frank Behrens Grant/research support from: Pfizer, Janssen, Chugai, Celgene, Lilly and Roche, Consultant of: Pfizer, AbbVie, Sanofi, Lilly, Novartis, Genzyme, Boehringer, Janssen, MSD, Celgene, Roche and Chugai, Peter Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Joseph F. Merola Consultant of: Merck, AbbVie, Dermavant, Eli Lilly, Novartis, Janssen, UCB Pharma, Celgene, Sanofi, Regeneron, Arena, Sun Pharma, Biogen, Pfizer, EMD Sorono, Avotres and LEO Pharma, Kevin Ding Employee of: Novartis, Pascale Pellet Shareholder of: Novartis, Employee of: Novartis, Luminita Pricop Shareholder of: Novartis, Employee of: Novartis, Iain McInnes Grant/research support from: Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Janssen, and UCB, Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Gilead, Janssen, Novartis, Pfizer, and UCB